Editorial - Pawlak, Mirosław (Studies in Second Language Learning and Teaching, 2016)
The last 2016 issue of Studies in Second Language Learning and Teaching includes six papers, five of which are reports of original research projects and one is a conceptual piece. The initial two contributions are concerned with different aspects of pragmatics, both with respect to the teaching of this subsystem and the process of its acquisition. In the first of these, Andrew D. Cohen addresses the crucial issue of how native and non-native teachers of second and foreign languages deal with sociopragmatic and pragmalinguistic features in their classes. He reports the findings of an online survey of 113 teachers of different additional languages from across the world, which demonstrated that while there exist many similarities between the native and non-native instructors, the former are often at an advantage, although they by no means confine themselves to reliance on their intuition. In the second, Qiong Li undertakes a synthesis of 26 original longitudinal research studies on naturalistic pragmatic development in adult learners with the purpose of identifying patterns of variation in the acquisition of pragmatic features and providing potential explanations for the occurrence of such variation. The analysis showed that there are differences in the rate of development of various aspects of pragmatics (e.g., speech acts vs. lexical features), which can be accounted for in terms of factors related to the target language (e.g., the frequency of the feature in the input), the situation (e.g., social status) and the learner (e.g., initial knowledge about the target feature). The following two papers shift the emphasis to the role of individual factors in the process of second language acquisition, more specifically the contributions of motivation and willingness to communicate (WTC). Ali Al-Hoorie reports the results of a survey study conducted among 311 young Arabic adult learners of English as a foreign language, providing evidence, somewhat in contrast to much previous research, that achievement in second language learning is a function of implicit attitudes to L2 speakers and L2 learning experience rather than the ought-to self or attachment to the L1 group, with such constructs as the ideal L2 self or intended effort being unrelated to success. The study by Mystkowska-Wiertelak investigated fluctuations in WTC of advanced learners of English during seven conversation classes which she taught over the period of one semester. Quantitative and qualitative analysis of the data gathered by means of self-assessment girds, interviews, questionnaires and detailed lesson plans indicated that WTC was indeed in a state of flux, both within single lessons and over time, with such changes being attributed to an intricate interplay of contextual and individual factors. The last two contributions focus on the role of critical thinking in foreign language learning. Jelena Bobkina and Svetlana Stefanova present a model of teaching critical thinking skills with the help of literature, arguing that such skills can be fostered through encouraging critical reader response to fictional work embedded in social phenomena as well as illustrating how this model can be applied to classroom practice. In the last paper, Paweł Sobkowiak underscores the interdependence of critical thinking and the development of intercultural competence, discussing the findings of a study of 20 coursebooks used in the Polish contexts and concluding that activities used in these coursebooks fall short of achieving either goal. As always, I am confident that all of the papers included in the present issue will provide food for thought to the readers and serve as a springboard for future empirical investigations that will help us better understand the exceedingly complex processes of second language learning and teaching.